Fast Mapping in Typically Developing Kannada Speaking Toddlers - Sushma M.; Amulya P Rao; Ranjini Mohan; Swapna N. (Journal of All India Institute of Speech and Hearing, 1970)
The ability to form a 'quick, initial, partial understanding of word's meaning' and thereby to learn and retain new words with only minimal exposure is known as Fast Mapping. Studies exploring fast mapping abilities especially in toddlers are limited, therefore research in this area would be highly valuable in understanding the way children accomplish the task of learning new words that add to their developing lexicon. Thus the present study was undertaken to investigate the fast mapping skills of toddlers by examining the effect of practice on the accessibility of the words in the lexical memory. Two groups of typically developing Kannada speaking children between the age of 16 to 20 months participated in the study. These children were taught the names of 24 unfamiliar objects over twelve training and testing sessions spread over a span of twenty four days. The amount of practice children had with individual words varied as a function of session. The experimental group underwent training and testing for all the sessions, while the control group were trained and tested during the first and last sessions only. The accuracy of identification, at every session was tabulated and subjected to statistical analysis. The results revealed that there was significant difference between the high practice words (words exposed to during all the sessions) of session '1' and Low practice words (words exposed to during the last session) of session '12' in both the groups. However, between the two groups, the performance on low practice words was not significant. Thus it can be concluded that fast mapping does occur in toddlers and learning some words primes the system to learn a novel set of words. Nevertheless, the present results should be interpreted with caution because of modest sample size considered.